Evaluation of Grants to Encourage Arrest Policies for Domestic Violence Cases in the State College, Pennsylvania, Police Department, 1999-2000 - Mastrofski, Jennifer Adams ([Verlag nicht ermittelbar], 2001)
This project was an 18-month long research-practitioner partnership to conduct a process evaluation of the State College Police Department's implementation of a grant to encourage arrest policies for domestic violence. The general goals of the process evaluation were to assess how and to what extent the State College Police Department's proposed activities were implemented as planned, based on the rationale that such activities would enhance the potential for increasing victim safety and perpetrator accountability systemically. As part of the grant, the police department sought to improve case tracking and services to victims by developing new specialized positions for domestic violence, including: (1) a domestic violence arrest coordinator from within the State College Police Department who was responsible for monitoring case outcomes through the courts and updating domestic violence policies and training (Part 1, Victim Tracking Data from Domestic Violence Coordinator), (2) a victims service attorney from Legal Services who was responsible for handling civil law issues for domestic violence victims, including support, child custody, employment, financial, consumer, public benefits, and housing issues (Part 2, Victim Tracking Data From Victim Services Attorney), and (3) an intensive domestic violence probation officer from the Centre County Probation and Parole Department who was responsible for providing close supervision and follow-up of batterers (Part 3, Offender Tracking Data). Researchers worked with practitioners to develop databases suitable for monitoring service provision by the three newly-created positions for domestic violence cases. Major categories of data collected on the victim tracking form (Parts 1 and 2) included location of initial contact, type of initial contact, referral source, reason for initial contact, service/consultation provided at initial contact, meetings, and referrals out. Types of services provided include reporting abuse, filing a Protection from Abuse order, legal representation, and assistance with court procedures. Major categories of data collected on the offender tracking form (Part 3) included location of initial contact, type of initial contact, referral source, reason for initial contact, service/consultation provided, charges, sentence received, relationship between the victim and perpetrator, marital status, children in the home, referrals out, presentencing investigation completed, prior criminal history, and reason for termination. Types of services provided include pre-sentence investigation, placement on supervision, and assessment and evaluation. In addition to developing these new positions, the police department also sought to improve how officers handled domestic violence cases through a two-day training program. The evaluation conducted pre- and post-training assessments of all personnel training in 1999 and conducted follow-up surveys to assess the long-term impact of training. For Part 4, Police Training Survey Data, surveys were administered to law enforcement personnel participating in a two-day domestic violence training program. Surveys were administered both before and after the training program and focused on knowledge about domestic violence policies and protocols, attitudes and beliefs about domestic violence, and the background and experience of the officers. Within six months after the training, the same participants were contacted to complete a follow-up survey. Variables in Part 4 measure how well officers knew domestic violence arrest policies, their attitudes toward abused women and how to handle domestic violence cases, and their opinions about training. Demographic variables in Part 4 include age, sex, race, education, and years in law enforcement.